2020
DOI: 10.3390/biom10020274
|View full text |Cite
|
Sign up to set email alerts
|

Ice Binding Proteins: Diverse Biological Roles and Applications in Different Types of Industry

Abstract: More than 80% of Earth’s surface is exposed periodically or continuously to temperatures below 5 °C. Organisms that can live in these areas are called psychrophilic or psychrotolerant. They have evolved many adaptations that allow them to survive low temperatures. One of the most interesting modifications is production of specific substances that prevent living organisms from freezing. Psychrophiles can synthesize special peptides and proteins that modulate the growth of ice crystals and are generally called i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 140 publications
(181 reference statements)
0
49
0
Order By: Relevance
“…Another group of genes that are important in cold adaptation were also found in the transcriptome studies, such as genes encoding for antifreeze proteins (AFPs). The AFPs play an important role to prevent the formation of intra- and extra-cellular ice-crystallization, thus enabling the cell to withstand fluctuating freezing temperatures, and consequently, cell death [ 54 , 55 ]. G. antarctica has nine genes encoding for AFPs and the gene expression analyses revealed that each AFP has diverse expression levels, depending on various factors including organism, temperature and environment [ 4 , 10 , 52 , 54 ].…”
Section: Molecular Adaptationmentioning
confidence: 99%
“…Another group of genes that are important in cold adaptation were also found in the transcriptome studies, such as genes encoding for antifreeze proteins (AFPs). The AFPs play an important role to prevent the formation of intra- and extra-cellular ice-crystallization, thus enabling the cell to withstand fluctuating freezing temperatures, and consequently, cell death [ 54 , 55 ]. G. antarctica has nine genes encoding for AFPs and the gene expression analyses revealed that each AFP has diverse expression levels, depending on various factors including organism, temperature and environment [ 4 , 10 , 52 , 54 ].…”
Section: Molecular Adaptationmentioning
confidence: 99%
“…A variety of temperature-induced enzymes such as cold-shock proteins (Csps) and heat-shock proteins (Hsps) are also involved in cold-shock resistance by regulating signaling cascades that protect damaged proteins and cofactors [ 50 ]. Moreover, various antifreeze proteins and polysaccharides such as trehalose, mannitol, and exopolysaccharides, which are constituents of biofilm, can act as cryoprotectants [ 51 ].…”
Section: Survival Strategies Of Extremophilic Microorganisms Undermentioning
confidence: 99%
“…The technique allows minimization of wastage with improved shelf life extension. Some of the popular conventional preservation techniques like heating, drying and freezing have been implemented in large industries (Pereira et al 2018 ; Białkowska et al 2020 ; Said 2020 ). However, it has been found that there are certain disadvantages in heat treatment and freezing methods such as food shrinkage, texture and nutrient loss and organic properties leading to a huge overall loss in the food product (Jayasena et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%